Analisis Efektivitas Kebijakan Manajemen User dan Firewall pada Sistem Operasi dalam Mencegah Akses Ilegal - Anisah Anisah; Cut Intan Efrina; Muhammad Lukmanul Hakim; Nadhirah Adzra Afifah Siregar; Yusra Putri Maulida (JIKUM: Jurnal Ilmu Komputer, 2026)
Information system security is a crucial aspect in managing modern operating systems as the threat of unauthorized access to information systems increases. Therefore, effective protection strategies such as user access management policies and firewall implementation are needed in operating systems. This study aims to analyze the effectiveness of user management and firewall policies in preventing unauthorized access to operating systems by comparing their implementations in Windows and Linux. The method used in this study is a qualitative approach through literature studies of various relevant research and case studies. The findings show that user management plays a role in controlling internal access rights by implementing the principle of least privilege, while firewalls function as an effective external defense layer in controlling network traffic. Both complement each other in maintaining system security. However, their success is highly dependent on the implementation of stable rules, accurate settings, and the competence of system administrators. By combining good policies and proper firewall configuration, operating systems can be more robust against various unauthorized access risks, thus maintaining data and infrastructure security.